Quiz_4 answer
Quiz_4 answer
Quiz_4 answer
2x−7
2 Find the values of x that satisfy x+1 <x−3
Strategy: Do the question lol (preliminary)
Solution 1: I don’t like this solution as you need to do casework. There are two cases: when x > −1 and
when x < −1 (and x = −1 doesn’t exist so I don’t care about it.). This is because if we multiply by x + 1
but if it is negative, we must flip the inequality sign. So,
C1: x > −1 Here we can just multiply accordingly to get 2x − 7 < (x − 3)(x + 1) and expand to get
2x − 7 < x2 − 2x − 3 and move everything to RHS to get 0 < x2 − 4x + 4 this gives 0 < (x − 2)2 so this is true
for all x ̸= 2. However, remember this is only talking about when x > −1 so we know that ] − 1, 2[∪]2, ∞[
is part of it.
C2: x < −1 Here all steps are the same but we must flip the inequality sign, getting 0 > (x − 2)2 which is
never true, so any x < −1 does NOT work.
Hence the answer is x ∈ ] − 1, 2[ ∪ ]2, ∞[
Solution 1.5: You can graph the function on the left to convince yourself that x < −1 doesn’t work after
solving C1 without knowing it’s a C1. This I think is fine and perfectly reasonable.
2x−7
Solution 2: Alternatively, if you don’t want to consider weird sign shit, move x − 3 over to get x+1 − x + 3
2x−7 x(x+1) 3(x+1) 2x−7 x2 +x 3x+3
and convert both to the same denominator to get x+1 − x+1 + x+1 and simplify to get x+1 − x+1 + x+1
2 2
2x−7−x −x+3x+3
now combine numerators, x+1 and we get −x x+1
+4x−4
.
Now last time we solved something similar by just considering the sign of the numerator/denominator and
plotting it on a graph. We can do the exact same thing here. Obviously, x + 1 changes signs at −1, and
−x2 + 4x − 4 changes signs at its zeroes. We can set −x2 + 4x − 4 = 0 and factor out −1 (do NOT multiply
by −1 or else you need to flip the sign anyways smh) to get −1(x2 − 4x + 4) = 0 which is ofc, −(x − 2)2 , so
this thing is negative except at x = 2 when its 0. So, we want only when the signs mismatch, this is when
x + 1 is positive so its all x > −1 and blah blah same thing as the end of solution 1.
1
2
3 f (x) = xx2 −1
+1 is defined for x ≤ 0. Find an expression for the
inverse function of f (x).
Strategy: Do the question lol (preliminary)
2
Solution: Replace f (x) with x and x with y to get x = yy2 −1
+1 , now for some algebra bash, follow along...
2 2 2 2
x(y +1) = y −1 expand, xy +x = y −1, move all y to the right, x+1 =q y 2 −xy 2 , factor y 2 , x+1 = y 2 (1−x),
x+1 x+1
divide by 1 − x, 1−x = y 2 and give birth to a square root, getting y = ± 1−x .
Now, because the domain of
√
f (x) is x ≤ 0, the range of f ]x[ (this is my inverse notation) must be y ≤ 0, and since k returns positive
r
x+1
values, we keep the negative root to make all of them negative, so our answer is f ]x[= −
1−x
Solution: At x = 2, the functions just need to be equal. Sub in x = 2 to get c(2) + 3 = c(4) + 1 and this
turns into 2c + 3 = 4c + 1 and 2 = 2c so c = 1
2
2
6 [GDC allowed] Consider the function f (x) = 3x − 4 + x−1 , where
x ∈ Z and x ̸= p.
6.1 Find the value of p.
Strategy: Do the question lol (preliminary)
Solution: If you graph it with your GDC you’ll see that the overall shape looks like the
image on the right. All you need to do is use the minimum and maximum features on
your calculator located next to the intersect/zero calculator and get those max/mins. The
highest the thing reaches on the bottom is −5.90 and the lowest thing thing reaches on the
top is 3.90, so your answer is y ∈ ] − ∞, −5.90] ∪ [3.90, ∞[